Tracing reading to the dark side: investigating the policy producing reading and readers in detention homes. Issue 6 (2nd November 2018) - Sundström Sjödin, Elin
ABSTRACT: Both inside and outside educational settings, reading literature is emphasized as something good, perhaps even something that makes us better people. This paper aims to open the 'black-boxed' conception of reading by studying how reading and (non)readers are conceptualized in relation to young people taken into custody. I examine a policy document describing a reading project in detention homes for young people as a case in which reading is perceived as having specific effects. Actor-network theory is used as a methodological approach to call attention to the way ideas, values, and knowledge about educational content are produced. The analysis shows that the seemingly coherent policy document produces radically different versions of what reading is and who the readers and non-readers are. I conclude that conceptualizations of reading and literacy always involve the creation of 'a dark side of reading'; the strong construction of 'reading as doing good' has marginalizing effects.